Playing the Numbers: The spurious promise of global trafficking statistics - Feingold, David A. (Anti-Trafficking Review, 2017)
‘Playing the numbers,’ ‘the numbers game,’ ‘the policy racket’: for those unfamiliar with American illegal lotteries and some of the legendary gangsters like Bumpy Johnson and Dutch Schultz that turned them into a major revenue stream for organised crime that still flourishes today, the concept was simple. The odds were disproportionately long, but poor people could bet very small amounts. It was, as they used to say, ‘a mugs game’; the organisers did well, while the poor lived on hope.